How formalization hinders different firm innovativeness types: Opening the black box with evidence from a service industry - (:unkn) unknown (World Scientific Publishing Co. Pte Ltd, 2014)
The purpose of this paper is to analyze the effects of organizational formalization on the behavioral, market, product, and process types of firm innovativeness as well as the interplay between these different innovativeness types. Based on data collected through a survey of the financial services industry in Turkey, the analyses show that formalization directly hinders both behavioral and market innovativeness. Moreover, as behavioral innovativeness influences product and process innovativeness, formalization's effect on these types of innovativeness are indirect. As expected, the study also finds that process innovativeness facilitates both product and market innovativeness and that product innovativeness foster market innovativeness. This study makes a contribution to the literature by examining the linkages between formalization in firms and the various firm innovativeness types, which have previously been studied only separately. The study thus provides a richer understanding of the relationship between formalization and firm innovativeness types. © 2014 World Scientific Publishing Company.
Keywords: Financial services; Firm innovativeness; Organizational formalization; Service innovation; Turkey